Effects of lipid levels on growth performance and glucose and lipid metabolism of adult Nile tilapia (Oreochromis niloticus) fed with high carbohydrate diets - Ningning Xie; Jianmin Zhang; Ming Jiang; Xiaolin Meng; Lixue Dong; Xing Lu; Hua Wen; Juan Tian (Aquaculture Reports)
A 10-week feeding trial was conducted to investigate the effects of lipid levels on growth performance and glucose and lipid metabolism of Nile tilapia (Oreochromis niloticus) fed with high carbohydrate diets. Experimental fish were fed with control diet (CON, containing 350 g/kg corn starch and 80 g/kg oil), high carbohydrate moderate lipid diet (HCML, D1, containing 550 g/kg corn starch and 80 g/kg oil) and high carbohydrate low lipid diet (HCLL, D2, containing 550 g/kg corn starch and 30 g/kg oil) respectively. Results showed that high carbohydrate diets hindered the healthy development of Nile tilapia by reducing growth performance and causing liver lipid deposition. Moderate lipid level alleviated these negative effects partly. Tilapia also showed an adaption to D1 and D2 diets with increased digestive enzyme activities and enhanced mRNA expression levels of glucose carriers. Furthermore, D1 and D2 diets influenced the glucose and lipid metabolism in muscle. There was an inhibition of gluconeogenesis with reduced content of G6P and expression of pck and a promotion of glycolysis with enhanced expression of pfkma and pfkmb. D2 diet increased the content of crude fat, content of ACC and expression level of fas and acc, which contributed to the synthesis of lipids. Comparatively, D1 diet stimulated the glycogen synthesis with increasing in the content of glycogen and expression of gys. In conclusion, high carbohydrate low lipid diet which could lead to increased lipid synthesis showed a greater negative impact on the healthy development of Nile tilapia compared to high carbohydrate moderate lipid diet.